اعجازِقرآن کا سائنسی پہلو(جدید سائنسی انکشافات کے تناظر میں ایک جائزہ): Scientific Miraculous Aspect of Holy Quran(A Review in the Light of Modern Scientific Revelations) - ‪Fouzia Batool (MEI, 2023)
Quran is a word of Allah Almighty revealed on the Holy Prophet (PBUH) with an eternal divine law (Shariah). This is the gospel of ceaseless blessings and a revolutionary lesson to deliver the man his actual status. Quran has numerous aspects and each one of them itself is a miracle. Ancient nations were not enough capable to be made trustee of immortal divine law (Shariah) as they were only familiar with the things they could see, touch or feel with senses. That’s reason they used to worship idols and were animist. So the prophets sent to them were given miracles according to their mental level. But when the human thoughts reached at the advanced level they were handed over the eternal divine law and code of life in the form of Quran, which is the prevalent miracle of Allah Almighty. The way Quran has been challenging the people for more than fourteen centuries itself proves the miraculous aspect of it. One of its miraculous aspects is scientific. The Quran draws attention to the signs and emblems present in the earth and heavens so that man should consider among them as a result of which he gains the knowledge about Allah and knows about the splendid blessings of Allah and becomes a thankful slave of Him. Therefore, it is important to clarify modern scientific inventions and discoveries in the interpretation of the Quran. The Quran made scientific discoveries fourteen centuries ago that are being revealed to scientists today. So in this article I have discussed the latest miracles of the Quran in the scientific field which would certainly be helpful for the researchers and for those seeking Allah Almighty.